Individual and Combined Acute Lethal Toxicity of Monocrotophos and 2,4-D on the Juveniles of Etroplus suratensis (Bloch) (Pisces: Cichlidae) - J.R., Rajasekharan Nair; T.V., Anna Mercy; George, Renu Maria (Fishery Technology, 2025)
The 48 h individual and combined lethal toxicity of monocrotophos (insecticide) and 2,4-D (herbicide) on the juveniles of Etroplus suratensis were determined. The 48 h LC of monocrotophos was 5.85 mg.l4 (5.02 to 6.69) and that of 2,4-D was 267.4 mg.l"1 (228.93 to 305.86). The median additive index and its range for the combined toxicity were worked out. The calculated value was -0.185 (-0.541 to 0.083). A simple or strictly additive toxicity is indicated for the mixture of monocrotophos and 2,4-D. This shows an enhanced potential of the individual toxicant for pollution in the natural bodies when they are applied sequentially and even simultaneously.